2018
DOI: 10.1111/joca.12205
|View full text |Cite
|
Sign up to set email alerts
|

Racial Differences in the Returns to Financial Literacy Education

Abstract: We examine financial literacy and the returns to financial literacy education, specifically focusing on the racial financial literacy gap. We confirm evidence that whites have higher financial literacy scores relative to minorities and that financial literacy increases with participation in financial literacy education. However, we find the benefit of participation in financial literacy education is higher for whites than that for minorities. Thus, the impact of being white alone persists, indicating a racial … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
32
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 45 publications
(39 citation statements)
references
References 45 publications
0
32
0
Order By: Relevance
“…Grinstein‐Weiss et al () suggest that low‐ and middle‐income Black and White students who face similar liquidity constraints and borrowing risks are at unequal risk of accumulating education debt. Further, there is evidence of a financial literacy gap with Whites having higher financial literacy scores than minorities despite financial literacy education (Al‐Bahrani, Weathers, and Patel ).…”
Section: Discussion Conclusion and Policy Implicationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Grinstein‐Weiss et al () suggest that low‐ and middle‐income Black and White students who face similar liquidity constraints and borrowing risks are at unequal risk of accumulating education debt. Further, there is evidence of a financial literacy gap with Whites having higher financial literacy scores than minorities despite financial literacy education (Al‐Bahrani, Weathers, and Patel ).…”
Section: Discussion Conclusion and Policy Implicationsmentioning
confidence: 99%
“…There are already some initiatives that help students make informed decisions about planning for, finding, and paying for college, such as the likelihood of finishing their degree and earnings in their field of study and budgeting under economic shocks (Avery and Turner ). However, there is a need for policymakers to examine if there is a systemic bias in the provision of financial literacy education (Al‐Bahrani, Weathers, and Patel ).…”
Section: Discussion Conclusion and Policy Implicationsmentioning
confidence: 99%
“…Previous studies have generally focused on sociodemographic and socioeconomic determinants, finding that the level of financial literacy depends on many characteristics such as gender, age, race (Al‐Bahrani, Weathers, and Patel ; Bucher‐Koenen et al ; Gerardi, Goette, and Meieret ; Lusardi and Tufano ; Van Rooij, Lusardi, and Alessie ), net family income, type of job, educational attainment, marital status, and the number of family members (Calamato ; Gerardi, Goette, and Meieret ; Monticone ; Shim et al ; Van Campenhout ).…”
mentioning
confidence: 99%
“…Literature suggests that those with special needs especially need better financial education (Mansfield and Pinto 2008 [27]). Our study responds to a call to examine the content of financial literacy curricula to ascertain what may be lacking in reaching minorities (Al-Bahrani et al (2018) [59]. This study fills a gap in the literature by identifying one specific curriculum for financial literacy that does have many culturally responsive elements: Practical Money Skills for Life.…”
Section: Discussionmentioning
confidence: 91%
“…As noted by Mittapalli et al (2009) [14], there is a dearth of culturally responsive curricula for financial literacy. Al-Bahrani et al (2018) [59] found that financial literacy education actually appears to widen the financial knowledge gap between whites and minorities. Literature suggests that those with special needs especially need better financial education (Mansfield and Pinto 2008 [27]).…”
Section: Discussionmentioning
confidence: 99%